Perceived Organizational Motives and Consumer Responses to Proactive and Reactive CSR - Groza, Mark D. (Journal of business ethics, 2011)
Corporate social responsibility (CSR) has emerged as an effective way for firms to create favorable attitudes among consumers. Although prior research has addressed the direct influence of proactive and reactive CSR on consumer responses, this research hypothesized that consumers’ perceived organizational motives (i.e., attributions) will mediate this relationship. It was also hypothesized that the source of information and location of CSR initiative will affect the motives consumers assign to a firms’ engagement in the initiative. Two experiments were conducted to test these hypotheses. The results of Study 1 indicate that the nature of a CSR initiative influences consumer attribution effects and that these attributions act as mediators in helping to explain consumers’ responses to CSR. Study 2 suggests that the source of the CSR message moderates the effect of CSR on consumer attributions. The mediating influence of the attributions as well as the importance of information source suggests that proper communication of CSR can be a viable way to inculcate positive corporate associations and purchase intentions.